Marginal staining of ultra-thin ceramic veneers - Renata Ragagnin Zago; Luciana Abitante Swarowsky; Gabriela Simões Teixeira; Marcela Marquezan; Alexandre Henrique Susin; Letícia Brandão Durand (Universidade Estadual de Campinas, 2020)
The pigmentation of the resin cement at the tooth/ceramic interface compromises the esthetic and longevity of ultra-thin ceramic veneers. Aim: The aim of this study was to evaluate marginal staining of ultra-thin ceramic veneers cemented to intact enamel (non-prepared) and prepared enamel. Methods: Thirty-two (32) permanent central incisors were selected and randomly divided into two groups: intact enamel (IE) and prepared enamel (PE). The ceramic veneers of PE group were bonded to the prepared enamel and the ceramic veneers of IE group were cemented directly onto the intact enamel, with no preparation. Both preparation and cementation were standardized and performed by a single operator. Each group was subdivided into two subgroups (n = 8) with different immersion media - coffee and water. After an immersion period of 10 days, stereomicroscope images were made at 20X magnification of the mesial, distal, cervical and incisal surface of each specimen. Three blinded, trained and calibrated examiners evaluated the images of the resin cement interface of each surface. The data were subjected to Kruskal‑Wallis and Mann‑Whitney statistical analysis. Immersion media and enamel preparation influenced the marginal staining of the tooth/ceramic interface. Results: When immersed in coffee, prepared interfaces presented greater marginal staining than unprepared interfaces. When immersed in water, there was no statistically significant difference between the groups. Conclusion: The cementation of ultra-thin ceramic veneers onto intact enamel is associated with less marginal staining and, consequently, improved esthetics.